2019
DOI: 10.1038/s41598-018-37881-0
|View full text |Cite
|
Sign up to set email alerts
|

Population structure and genetic differentiation of tea green leafhopper, Empoasca (Matsumurasca) onukii, in China based on microsatellite markers

Abstract: The tea green leafhopper, Empoasca (Matsumurasca) onukii Matsuda, is one of the dominant pests in major tea production regions of East Asia. Recent morphological studies have revealed variation in the male genitalic structures within and among populations. However, the genetic structure of this pest remains poorly understood. This study explores the genetic diversity and population structure of this pest in nineteen populations from the four main Chinese tea production areas using microsatellite markers, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 43 publications
8
26
0
Order By: Relevance
“…Our analyses of phylogenetic and genetic structure confirmed the genetic differences between group I (samples from Yunnan) and the other groups, as shown in a previous study based on microsatellites [5]. However, this previous study suggested four main genetic groups (K = 4) [5]. This may be because the present study collected much more samples around China (54 locations in 22 provinces) than the other one (22 19 locations in 13 provinces) and used a greater number of genetic markers (whole-genome SNPs vs. microsatellite markers).…”
Section: Evolutionary History Is Inconsistent Between Tgl and Tea Cultivarssupporting
confidence: 90%
See 1 more Smart Citation
“…Our analyses of phylogenetic and genetic structure confirmed the genetic differences between group I (samples from Yunnan) and the other groups, as shown in a previous study based on microsatellites [5]. However, this previous study suggested four main genetic groups (K = 4) [5]. This may be because the present study collected much more samples around China (54 locations in 22 provinces) than the other one (22 19 locations in 13 provinces) and used a greater number of genetic markers (whole-genome SNPs vs. microsatellite markers).…”
Section: Evolutionary History Is Inconsistent Between Tgl and Tea Cultivarssupporting
confidence: 90%
“…This may be because the present study collected much more samples around China (54 locations in 22 provinces) than the other one (22 19 locations in 13 provinces) and used a greater number of genetic markers (whole-genome SNPs vs. microsatellite markers). We observed that individuals from different groups were interspersed (Figures 4B and C), possibly reflecting gene flow across location, as observed in the previous study [5].…”
Section: Evolutionary History Is Inconsistent Between Tgl and Tea Cultivarssupporting
confidence: 80%
“…The observed level of heterozygosity was compared to the expected HetEQ using the intermediate two-phased model (TPM), due to its suitability for microsatellite data 81 , 82 . The TPM was applied with 95% of the mutations following a two-phase mutation pattern and a variance among multiple steps of 12 83 , with deviations from equilibrium determined using Wilcoxon’s Sign Rank tests, which are most suitable in instances where less than 20 loci are used 81 . Effective population size ( N e ) was estimated assuming a closed population with discrete generations and random variance in reproductive success using the program NeEstimator v2.01 84 .…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies demonstrate the importance of quantifying phylogenetic relatedness between species to understand how evolutionary history and colonization dynamics influence diversity within communities [9,10]. Phylogenetic diversity (PD) also plays an important role in conservation [11], for better prioritizing phylogenetically diverse areas, as well as for preserving ecosystem function and associated ecosystem services [12].…”
Section: Introductionmentioning
confidence: 99%